Harlekin und Der kleine harlekin - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2010)
HARLEKIN ( HARLEQUIN ) and DER KLEINE HARLEKIN ( THE LITTLE HARLEQUIN )for clarinet with introduction to HARLEKIN by K. Stockhausen ( Lisbon 1990 )( Colour film by Henning Lohner ) ( Archive No. 3/ 1 )Contents: Introduction to HARLEKIN followed by concert peformance at the Grande Auditorio of theGulbenkian Foundation Lisbon on May 7th1990.Concert performance of DER KLEINE HARLEKIN in Weingarten on October 23rd 1992 ( Project No. 34/1 ).Clarinet: Suzanne Stephens.